Analysis of muscular activity and dynamic response of the lower limb adding vibration to cycling (2018)
Vibration in cycling has been proved to have undesirable effects over health, comfort and performance of the rider. In this study, 15 participants performed eight 6-min sub-maximal pedalling exercises at a constant power output (150W) and pedalling cadence (80 RPM) being exposed to vibration at different frequencies (20, 30, 40, 50, 60, 70 Hz) or without vibration. Oxygen uptake (VO2), heart rate (HR), surface EMG activity of seven lower limb muscles (GMax, RF, BF, VM, GAS, SOL and TA) and 3-dimentional accelerations at ankle, knee and hip were measured during the exercises. To analyse the dynamic response, the influence of the pedalling movement was taken into account. The results show that there was not significant influence of vibrations on HR and VO2 during this pedalling exercise. However, muscular activity presents a significant increase with the presence of vibration that is influenced by the frequency, but this increase was very low (< 1%). Also, the dynamic response shows an influence of the frequency as well as an influence of the different parts of the pedalling cycle. Those results help to explain the effects of vibration on the human body and the influence of the rider/bike interaction in those effects.